Integrated hepatitis C treatment is associated with improved retention and success in outpatient treatment for opioid use disorder at a private clinic - Losikoff, Phyllis; Bosse, Jordon D.; Martin, Stephen A.; Wilson, Amanda; Chiodo, Lisa M. (Frontiers in Psychiatry, 2022)
Background: Direct acting antiretrovirals (DAA) are effective for individuals who are infected with chronic hepatitis C virus (HCV), yet many people go without access to these lifesaving treatments. Materials & Methods: We conducted a non-randomized study evaluating treatment data for patients in outpatient treatment for opioid use disorder (OUD) at a private clinic. Patients who were HCV-positive, had been in OUD treatment for at least four weeks, and engaged in integrated HCV treatment with DAA (co-located within their treatment for OUD) were compared to patients with HCV who only received OUD treatment. We evaluated HCV cure; OUD medication adherence, treatment utilization and retention; and illicit substance use for those engaged in treatment between 9/2016 and 1/2018. Results: 74 patients completed integrated HCV-OUD treatment with DAA, with 87.8% achieving cure. Of the 66 who completed treatment and were subsequently evaluated for sustained viral response 98.5% were cured. Patients who received integrated HCV and OUD treatment in our clinic, stayed in OUD treatment longer, demonstrated higher OUD medication adherence, and used less opioids or cocaine compared to HCV-infected patients (n=572) being treated only for OUD. Discussion: We have reported on a reproducible intervention that lends itself to outpatient OUD treatment. Analyses demonstrate the potential positive impact HCV treatment has on OUD recovery, including reduction in opioid and cocaine use and increased retention in care Conclusion: Co-locating HCV treatment with existing OUD treatment is feasible, effective, and demonstrates positive outcomes for the treatment of both conditions.